Pergeseran Struktur Ekonomi dan Identifikasi Sektor Potensial Wilayah Pengembangan di Kabupaten Klaten Tahun 2009-2013 - Prasetyo, Arif Nur; , Dr. Didit Purnomo, SE. M.Si (2016)
This research to analyze determine the allocation effects that occurred in agriculture and non-agricultural sectors in the district of Klaten seen from Klaten district GDP. This type of research used in this research is quantitative research. In this study, the data used is the data in this study use traditional secondary data obtained from the office of the Central Bureau of Statistics as well as offices - other relevant government departments in the district of Klaten in Central Java Province 2009-2013. The data analysis technique used in this study adalahShift Share Modified Esteban marquillas (SS - EM). Based on analysis of the data in this study can be concluded that the sectors that have the effect of competition (C'ij) is positive, it means being able to compete with other regions. Since the year 2009-2013, Klaten district can be said to experience a decline in competitiveness in various sectors, while the allocation of economic sectors seen dariefek Klaten district in 2009-2013, which has the potential to become the leading sectors are the sectors excavation / mining, building / construction, trade, hotels and restaurants as well as the services sector. While from the year 2009-2013, no ongoing basis over a period of 5 years have a competitive advantage and specialization.